Comparison of FilmArray and Quantitative Real-Time Reverse Transcriptase PCR for Detection of Zaire Ebolavirus from Contrived and Clinical Specimens - Southern, Timothy R. (J Clin Microbiol, 2015)
Rapid, reliable, and easy-to-use diagnostic assays for detection of Zaire ebolavirus (ZEBOV) are urgently needed. The goal of this study was to examine the agreement among emergency use authorization (EUA) tests for the detection of ZEBOV nucleic acids, including the BioFire FilmArray BioThreat (BT) panel, the FilmArray BT-E panel, and the NP2 and VP40 quantitative real-time reverse transcriptase (qRT) PCR assays from the Centers for Disease Control and Prevention (CDC). Specimens used in this study included whole blood spiked with inactivated ZEBOV at known titers and whole-blood, plasma, and urine clinical specimens collected from persons diagnosed with Ebola virus disease (EVD). The agreement for FilmArray and qRT-PCR results using contrived whole-blood specimens was 100% (6/6 specimens) for each ZEBOV dilution from 4 × 10(7) to 4 × 10(2) 50% tissue culture infective dose (TCID(50))/ml, as well as the no-virus negative-control sample. The limit of detection for FilmArray and qRT-PCR assays with inactivated ZEBOV, based on duplicate positive results, was determined to be 4 × 10(2) TCID(50)/ml. Rates of agreement between FilmArray and qRT-PCR results for clinical specimens from patients with EVD were 85% (23/27 specimens) for whole-blood specimens, 90% (18/20 specimens) for whole-blood specimens tested by FilmArray testing and matched plasma specimens tested by qRT-PCR testing, and 85% (11/13 specimens) for urine specimens. Among 60 specimens, eight discordant results were noted, with ZEBOV nucleic acids being detected only by FilmArray testing in four specimens and only by qRT-PCR testing in the remaining four specimens. These findings demonstrate that the rapid and easy-to-use FilmArray panels are effective tests for evaluating patients with EVD.